The influence of COVID- 19 on buying behavior of consumers in Kathmandu city - Rai, Bharat; Bhandari, Dila Ram (NCC Journal, 2022)
The main goal of this research was to analyze the impact of COVID-19 on buying behaviors of consumers during lockdowns in Kathmandu city. Fear of health, fear of economy, and fear of scarcity were taken as independent variables to measure the buying behaviors of consumers. The study used positivist epistemology with predetermined hypotheses and a deductive approach with a single ontological foundation. The study used a quantitative method. To obtain the primary data, and questionnaire based on a seven-point Likert scale was utilized. The population for this study was comprised of customers of consumer goods in and a sample size of 395 was used. In this study, a convenient sampling technique and a causal-comparative research design were used. Path analysis through Structural Equation Modeling was utilized to determine the effect of influencing variables on buying behaviors of consumers. The regression path analysis result found that fear of the economy and fear of scarcity had a substantial effect on consumer buying behavior. In contrast, the fear of health had not significantly affected consumer buying behavior. The results provide future scholars and business people with a road map to view the emerging context of market development.